2015
DOI: 10.1007/s11085-015-9547-2
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation and Electrical Behavior of Mn-Co-Coated Crofer 22 APU Steel Produced by a Pack Cementation Method for SOFC Interconnect Applications

Abstract: An issue associated with chromia-scale formation on ferritic stainless steels is an associated increase in electrical resistance over time, due to the oxide growth. Further, the migration of chromium via chromia-scale evaporation into solid oxide fuel cell (SOFC) cathodes can result in degradation in cell electrochemical performance. In this research, manganese and cobalt were deposited by the pack cementation method onto Crofer 22 APU ferritic stainless steel. Isothermal and cyclic oxidation was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 58 publications
2
6
0
Order By: Relevance
“…The post-test analysis of the stacks (of this paper) after operation has shown Cr-Mn oxide scale formation with thicknesses -depending on the overall operating time -up to several µm. These results are in good agreement with the results of other research groups (30,31,32). The tested stacks in the present paper contained Cr evaporation protection layers on the cathode side of the bipolar sheets.…”
Section: Stack Repeat Unit With High Power Performance (Ru#1)supporting
confidence: 92%
“…The post-test analysis of the stacks (of this paper) after operation has shown Cr-Mn oxide scale formation with thicknesses -depending on the overall operating time -up to several µm. These results are in good agreement with the results of other research groups (30,31,32). The tested stacks in the present paper contained Cr evaporation protection layers on the cathode side of the bipolar sheets.…”
Section: Stack Repeat Unit With High Power Performance (Ru#1)supporting
confidence: 92%
“…The ASR of AISI 441 is about 30 mΩ cm 2 [91,92], similar to that of ZMG 232 [91]. The model alloys in a family of FeCrMn(La/Ti) leading to the development of Crofer 22 APU have ASRs in the range of 10-15 mΩ cm 2 [91] lower than the ASR of Crofer 22 APU which is in the range of 35-50 mΩ cm 2 as reported by Hosseini et al [93] and Ebrahimifar and Zandrahimi [94]. At shorter oxidation period i.e.…”
Section: Area Specific Resistancesupporting
confidence: 69%
“…Fig. 6.3 shows ASRs of the bare ferritic stainless steels after oxidation at 800 ºC in air [88][89][90][91][92][93][94]. The first and second bars from the left present, respectively, the results after 100 and 200 h of exposure.…”
Section: Area Specific Resistancementioning
confidence: 99%
“…Meanwhile, Fe in the substrate and Co ions diffuse through the Cr 2 O 3 layer and react to form CoFe 2 O 4 . In addition, according to the Cr 2 O 3 –Fe 2 O 3 phase diagram, it can be observed that Cr 2 O 3 and Fe 2 O 3 are soluble . They possess the identical crystal structures and similar lattice constants: the a values of Cr 2 O 3 and Fe 2 O 3 are 0.4959 and 0.5036 nm, respectively, whereas the c values of them are 1.3594 and 1.3749 nm, respectively .…”
Section: Resultsmentioning
confidence: 98%
“…The diffraction peaks of the AS22-Ar sample correspond to the substrate, Co, Cr 2 O 3 , CoFe 2 O 4 , and Co 3 Fe 7 phases (Figure 6a). The entrapped O 2 in the pack mixture leads to the 26 They possess the identical crystal structures and similar lattice constants: the a values of Cr 2 O 3 and Fe 2 O 3 are 0.4959 and 0.5036 nm, respectively, whereas the c values of them are 1.3594 and 1.3749 nm, respectively. 26 The result indicates that Cr 2 O 3 and Fe 2 O 3 can mutually overlay.…”
Section: Phases and Morphologies Of Coating In Armentioning
confidence: 99%